Intelligent impedance based fault-location for zonal power systems - Rose, Chris; Thomas, David W.P.; Sumner, M.; Christopher, Edward; Lopez Arevalo, Saul (2014)
A laboratory based demonstrator has been constructed to study the Active Impedance Estimation (AIE) technique as a means of locating faults on a power system. The demonstrator has been used to verify results from simulation experimentally. The AIE system and associated signal processing are presented and some of the issues that have been encountered are discussed. The presented simulation and experimental results presented both validate the method used.